2014
DOI: 10.3390/ijerph110606459
|View full text |Cite
|
Sign up to set email alerts
|

The Case in Favor of E-Cigarettes for Tobacco Harm Reduction

Abstract: A carefully structured Tobacco Harm Reduction (THR) initiative, with e-cigarettes as a prominent THR modality, added to current tobacco control programming, is the most feasible policy option likely to substantially reduce tobacco-attributable illness and death in the United States over the next 20 years. E-cigarettes and related vapor products are the most promising harm reduction modalities because of their acceptability to smokers. There are about 46 million smokers in the United States, and an estimated 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
(30 reference statements)
3
26
2
Order By: Relevance
“…Smokeless tobacco and, more recently, e-cigarettes have been promoted as a harm reduction strategy for smokers who are unable or unwilling to quit1 2 3 4 on the assumption that as those who are able and willing to quit do so, a group of hardcore smokers will be left behind. The concept of harm reduction was first proposed by Russell5 6 when he suggested offering smokers a less harmful source of nicotine than combusted cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…Smokeless tobacco and, more recently, e-cigarettes have been promoted as a harm reduction strategy for smokers who are unable or unwilling to quit1 2 3 4 on the assumption that as those who are able and willing to quit do so, a group of hardcore smokers will be left behind. The concept of harm reduction was first proposed by Russell5 6 when he suggested offering smokers a less harmful source of nicotine than combusted cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…3 Electronic cigarettes (e-cigarettes) represent a new prospect in harm reduction from tobacco use. 4,5 However, studies demonstrating the efficacy of e-cigarettes as harm reduction devices are lacking. 6,7 While several laboratory studies have shown that e-cigarette aerosol contains significant amounts of nicotine and reduced levels of toxicants compared to tobacco smoke, [8][9][10] laboratory machine yields do not necessarily reflect toxicant exposure in an individual smoker.…”
Section: Introductionmentioning
confidence: 99%
“…Except for American Cancer Society studies on light and low tar cigarettes [14] we have no population-based studies that allege differences in either addiction or risk of potentially fatal tobacco-related illness by chemical or component of the tobacco smoke within a given class of tobaccorelated products. By disregarding the studies by class of product, FDA ignores the large and growing body of evidence that e-cigs, as a class, are likely to be far less hazardous and less addictive than cigarettes [5,6,15].…”
Section: Introductionmentioning
confidence: 99%
“…British authorities came out with the Public Health England report endorsing tobacco harm reduction using e-cig products to reduce tobacco-related illness and death [4]. We now have American, Canadian, and British reports showing that e-cigs are effective in helping smokers cut down and quit [4][5][6][7][8] and doing so without recruiting significant numbers of nonsmoking teens to nicotine addiction. This tips e-cigs from a product seen as dangerous and highly addictive to a product that should be seen as having potential public health benefits well in excess of any potential harms; benefits not likely achievable by any other means.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation